English as a Foreign Language Teachers’ Critical Thinking Ability and L2 Students’ Classroom Engagement - Yan, Ziguang (Frontiers in Psychology, 2021)
Critical thinking has been the focus of many studies considering the educational and social contexts. However, English as a foreign language (EFL) context is the one in which studies about critical thinking and its link to classroom engagement have not been carried out as much as expected. Hence, this study investigated to understand the association between EFL teachers’ critical thinking ability and students’ classroom engagement to get a broader understanding of the impact critical thinking has on students’ success. To do this, firstly, both variables of this study are defined and explicated. Then, the relationship between critical thinking and students’ classroom engagement is discussed. Finally, the implications of this research and also its limitations along with suggestions for further studies are put forward.